Pengaruh Pertumbuhan Penjualan, Kepemilikan Institusional, Kepemilikan Manajerial, dan Komisaris Independen Terhadap Tax Avoidance Pada Perusahaan Kosmetik dan Industri Rumah Tangga yang Terdaftar di Bursa Efek Indonesia - Alfitiara Fitriana Shiddiq; Idel Eprianto; Amor Marundha (Mulia Pratama, 2023)
This study examines an effect of Sales Growth, Institutional Ownership, Managerial Ownership, and Independent Commissioners toward Tax Avoidance. The population in this study are cosmetics and home industry companies listed on the Indonesia Stock Exchange for the 2016-2020 period. Sampling in this study was carried out by purposive sampling method with predetermined criteria, with 35 data samples obtained from the population. The type of data used is secondary data obtained from annual financial reports for the 2016-2020 period. Hypothesis testing uses the Multiple Linear Regression analysis method using the SPSS version 21 application. The results show that Sales Growth do not affect on Tax Avoidance, and Institutional Ownership affects Tax Avoidance. Managerial Ownership influences Tax Avoidance. Independent Commissioners do not affect Tax Avoidance. Variable Sales growth, institutional Ownership, managerial Ownership, and independent commissioners simultaneously affect 32.4% of tax avoidance.